THE EFFECT OF VIRGIN COCONUT OIL ON LYMPHOCYTE AND CD4 IN CHICKEN VACCINATED AGAINST Avian Influenza VIRUS - Yuniwarti, E.Y.W.; Asmara, W.; Artama, W.T.; Tabbu, C.R. (Diponegoro University, 2012)
This research aimed to find preventing alternative of avian influenza (AI) disease in broiler chickenby increasing body immune. Lymphocyte T would directly react to antigen presented to the cell surfaceby antigen presenting cell (APC). Th-CD4 interaction functioned to maintain Th-APC bond intactduring specific antigen activation. Fatty acid in virgin coconut oil (VCO) was potential asimmunostimulant, which therefore could increase chicken immunity through the increase of lymphocyteT and Th-CD4. This research used 40 one-day-old broiler chickens. The method applied was CompletelyRandomized Factorial Design in which the first factor was two levels of vaccine, namely groups of AIvaccinated and unvaccinated. The second factor was four levels of VCO namely 0, 5, 10, 15 mL/kg feed.Day Old Chick (DOC) were divided into eight treatment groups and repeated five times. Feed and waterwere given ad libitum for four weeks. The result showed that the number of lymphocyte and Th-CD4 inchickens given 10 mL per kg feed and vaccinated with AI was higher than that in chickens given VCOwithout AI vaccine.